Manajemen Sarana dan Prasarana Pendidikan sebagai Penunjang Keberhasilan Belajar di MI Yaqin Kaliwangkok Desa Kaliwangkok - Puji Yani; Desti Septiana Putri; Ahmad Izzuddin (Pendidikan Al-Gafari, 2024)
Facilities and infrastructure management is a part of school administration and is also an area of work for the principal as the school administrator. This research aims to determine the management of educational facilities and infrastructure in schools to support successful learning. With a problem formulation, what is the quality of school facilities and infrastructure at MI Yaqin Kaliwangkok, how is the management of school facilities and infrastructure in creating a comfortable learning environment, and finally what are the obstacles and challenges for facilities and infrastructure in supporting successful learning at MI Yaqin Kaliwangkok? This research uses a qualitative descriptive approach, the subjects of this research are the principal, deputy head of facilities, and several subject teachers, and the informants in this research are the research subjects themselves. The methods used in collecting data in this research were observation, interviews, and documentation. The validity of the data with the credibility of the source and method is then analyzed using an interactive model consisting of data collection, data reduction, data presentation, and conclusion. The results of this research can conclude that the educational facilities and infrastructure at MI Yaqin Kaliwangkok can be managed well if the management of the facilities and infrastructure runs smoothly.